Crop-standard interactions in Black pepper(piper NigrumL.) - Manjusha C M (Department of Plantation crops and Spices, College of Horticulture, 2007)
Black pepper, known as the King of Spices, is the most widely used spice in the world. Providing ideal support plays an important role in successful establishment of black pepper plantation. A study was carried out at the Department of Plantation Crops and Spices, College of Horticulture to unravel the interaction patterns of the Black pepper vines with different standards (supports) and to select the standard(s) ideal for trailing pepper.